Business plan Shakaboom Printing Studio / Shahrul Abdul Rahman ... [et. al] - Abdul Rahman, Shahrul; Mohamad Daud, Muhammad Izzariq; Abdul Jalil, Fudayi; Wilfred, Owenn; Abang Nazri, Abang Ahmad Farique Danial; Patahorrahman, Lutfur Rahman Ansari (2022)
ShakaBoom Printing is a printing shop in Kota Samarahan, Sarawak, Malaysia that provides a one-stop solution forall ofyour printing, scanning, lamination, copying, binding, graphic and architecture design needs. Our policy is to collaborate with our customers in a way that benefits both ofus in terms of cost, time, and product quality. The majority of our products are available for same-day and rush printing. We have invested in learning about and acquiring cutting-edge technology in this field in order to stay one step ahead of our competitors while providing first-rate print quality . Our Principles is to Create the highest quality product in the shortest amount of time while maintaining a good price-performance ratio. We aim to bring any concept, any idea, to life.